Abstraction in an Object-Oriented Analysis Method - Lee, Sai Peck; Rolland, Colette (Malaysian Journal of Computer Science, 1997)
The recent interest in object-oriented analysis has resulted in the introduction of abstraction in the analysis phase of information systems development life cycle. Abstractionhas been proven to be a powerful object- oriented construct through which software complexity can be reduced and software productivity can be improved. Our main aim in this paper is to provide the support of abstraction for both the statics and dynamics of an information system in an object-oriented analysis method. In this way, it allows the analyst to view the basic characteristics of major components of an information system at different perspectives.